Learning biographies in a European space for social mediation - Evans, Rob (2019)
Within the framework of a European Erasmus+ project, trainee mediators were interviewed about their experience. The encounters took place in unstructured, in-depth qualitative biographical-narrative interviews, in which individuals who are engaged in dialogic interaction create shared understanding and give meaning to their stories. The interview is interactive, co-constructed. The detail of the interview language documents how meaning-making takes place, and how this is affected by group belonging, ethnic or cultural discourses, as well as gender, age, professional and educational relationships, and so on. The interview is sensitive to language resources and their use in the co-construction of meaning. This paper, using extracts from one biographical narrative, shows that the languaged form that these narratives of the biographical learning of mediators take can offer insight into the learning processes triggered by learning in communities of practice, and that the creation of a common space of experience can be heard as it emerges in biographical talk. Biographical resources, biographicity, and their relationship with language and society are considered, and in the interview narratives the creation of a learning space, a space for the development and unfolding of notions and practices of mediation can be observed, heard and shared.